Superhydrophobic STA@PF@Cu2O modified wood with photocatalytic degradation properties for efficiency oil/water separation. Issue 6 (December 2021) - Xia, Sengwei; Cheng, Ruifeng; Zhan, Ke; Lu, Quanxiong; Jiang, Haiqiu; Yi, Tengfei; Morrell, Jeffrey J.; Zhang, Lianpeng; Du, Guanben; Gao, Wei
Abstract: The potential for coatings using Cu2 O nanostructures combined with stearic acid (STA) and phenol formaldehyde (PF) resin to selectively sorb oils from oil/water mixtures was explored on balsa wood ( Ochroma pyramidale ). Wood samples coated by immersion in STA@PF@Cu2 O nanostructures absorbed 1.6–3.9 times their weight from a wide range of oil and organic solvents with absorption capacity generally increasing with oil density. Separation efficiency of the coated balsa was above 90% for several oil/water mixtures, and the material surface could be regenerated up to 30 times by exposure to visible light while still retaining up to 94% efficiency. For example, a 320 min light exposure of coated samples used to sorb methylene blue resulted in 99.8% degradation with photocatalytic reaction rate constants reaching 0.013 min –1 . The coating represents an easily applied, cost effective and efficient system for oil sorption or oil/water sorption for spill-cleanup or wastewater treatment. Graphical Abstract: ga1 Highlights: Cu2ONPs was fixed on balsa wood to endow the function of oil/water separation. Oil adsorption, oil/water separation and photocatalytic capabilities were achieved. Wood samples absorbed mostly 3.9 times their weight from oils and organic solvents. Separation efficiency of the modified balsa was above 90% for oil/water mixtures. 99.8% methylene blue was catalytically degraded under visible light.